Thailand's International Meditation Centers: Tourism and the Global Commodification of Religious Practices - Brooke Schedneck (2018)
© 2015 Brooke Schedneck. All rights reserved. This book explores contemporary practices within the new institution of international meditation centers in Thailand. It discusses the development of the lay vipassana meditation movement in Thailand and relates Thai Buddhism to contemporary processes of commodification and globalisation. Through an examination of how meditation centers are promoted internationally, the author considers how Thai Buddhism is translated for and embodied within international tourists who participate in meditation retreats in Thailand. Shedding new light on the decontextualization of religious practices, and raising new questions concerning tourism and religion, this book focuses on the nature of cultural exchange, spiritual tourism, and religious choice in modernity. With an aim of reframing questions of religious modernity, each chapter offers a new perspective on the phenomenon of spiritual seeking in Thailand. Offering an analysis of why meditation practices appeal to non-Buddhists, this book contends that religions do not travel as whole entities but instead that partial elements resonate with different cultures, and are appropriated over time.